Occupational Therapy Practitioners' Knowledge, Comfort, and Competence Regarding Youth Suicide. (October 2020) - Kirby, Anne V.; Terrill, Alexandra L.; Schwartz, Ariel; Henderson, Jarrett; Whitaker, Brandi N.; Kramer, Jessica
Suicide rates for young people are climbing in the United States and worldwide. Increasing rates of youth suicide are of concern to occupational therapy (OT) practitioners in pediatric settings, yet the profession's role in this area is poorly defined. To understand OT practitioners' awareness and needs related to youth suicide, we administered a survey including objective (e.g., knowledge of suicide-related facts) and subjective items (open- and close-ended questions) related to youth suicide to 134 OT practitioners working in pediatric settings. Only 5.2% of respondents correctly answered four items about youth suicide facts and only 32% reported they had received suicide-focused education. Just under half (45%) of respondents were able to identify all best practice responses to clinical scenarios related to youth suicide; older practitioner age was the only significant predictor of best practices. OT practitioners in pediatric settings would benefit from youth-focused suicide education and training.